2017
DOI: 10.1121/1.4977748
|View full text |Cite
|
Sign up to set email alerts
|

The influence of signal type on perceived reverberance

Abstract: Currently, architectural room acoustic metrics make no real distinction between a room impulse response and the auditory system's internal representation of a room. These metrics are generally based on impulse responses, and indirectly assume that the internal representation of the acoustic features of a room is independent of the sound source. However, while a room can be approximated as a linear, time-invariant system, auditory processing is highly non-linear and varies a great deal over time in response to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…Such a source-filter characterization allows to characterize rooms as LTI systems. The results of this paper are in line with previous findings (Klockgether and van de Par, 2016;Teret et al, 2017) and may be used as evidence that the perception of room acoustic parameters depends on the context for which the room is used and this is contrary to the idea of an LTI system.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Such a source-filter characterization allows to characterize rooms as LTI systems. The results of this paper are in line with previous findings (Klockgether and van de Par, 2016;Teret et al, 2017) and may be used as evidence that the perception of room acoustic parameters depends on the context for which the room is used and this is contrary to the idea of an LTI system.…”
Section: Discussionsupporting
confidence: 91%
“…Evidence against the LTI assumption is given by Teret et al (2017), who asked 8 participants to match the perceived RT of subsequent signal pairs using either identical or different signals with varying degrees of reverberation. They found that the participants' responses were more accurate when the task was conducted with identical signals.…”
Section: Introductionmentioning
confidence: 99%
“…Literature provides only indirect evidence for this matter. It has been observed that the absolute amount of perceived reverberation differs between different signal types, e.g., vocal stimuli are typically perceived more reverberant than stimuli without vocals (Frissen et al, 2009;Teret et al, 2017). Such inaccuracy in perceiving the absolute levels of room acoustic features with different source signals also possibly makes recognizing individual rooms more difficult.…”
Section: Introductionmentioning
confidence: 99%
“…The differences in calculation method lead to distinct advantages and disadvantages of the parameters. As P REV is based on a running signal, this parameter can account for the influence of sample on reverberance (Osses Vecchi et al, 2017), which can be an important contributor to reverberance (Teret et al, 2017). Furthermore, P REV can estimate different characteristics of reverberance (such as stopped reverberance, running reverberance, and overall reverberance) (Morimoto and Asaoka, 2004) on the basis of analysing a selected part of a sample, and can be calculated both from audio recordings and during a live concert situation.…”
Section: Introductionmentioning
confidence: 99%